Dampak Paparan Konten Negatif di TikTok dan Instagram terhadap Kesehatan Mental Siswa: Kajian Literatur - Rizki Misbah Hidayat; Abdul Rifki; Ichsan Fauzi Rachman (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
The rapid growth of social media platforms, particularly TikTok and Instagram, has exposed students to various types of content—both constructive and harmful. Negative content such as toxic comments, body shaming, false self-image, and hate speech can pose serious risks to students’ mental health. This study aims to explore the psychological impact of such exposure among junior and senior high school students using a literature review approach. The method involved a systematic analysis of relevant academic publications from the past five years (2020–2025), focusing on the effects of negative digital content on students’ mental well-being. The findings indicate that frequent exposure to toxic comments, body shaming, unrealistic portrayals, and cyberbullying correlates with increased anxiety, depression, low self-esteem, and sleep disturbances. These outcomes emphasize the need for improved digital literacy, stronger parental and educational supervision, and preventative strategies in schools to support students in navigating social media responsibly. This study is expected to provide a theoretical foundation and practical considerations for future educational and psychosocial policies addressing the mental health impacts of social media on adolescents.